Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Encontre: } f \circ g(x) \]

Ask by Thornton Burgess. in Brazil
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

A composição das funções \( f \) e \( g \) é \( f \circ g(x) = 6x - 5 \).

Solution

Para encontrar a composição das funções \( f \) e \( g \), denotada como \( f \circ g(x) \), precisamos substituir \( g(x) \) na função \( f(x) \). 1. **Identificar as funções:** - \( f(x) = 3x + 4 \) - \( g(x) = 2x - 3 \) 2. **Substituir \( g(x) \) em \( f(x) \):** \[ f \circ g(x) = f(g(x)) = f(2x - 3) \] 3. **Substituir \( 2x - 3 \) na função \( f \):** \[ f(2x - 3) = 3(2x - 3) + 4 \] 4. **Realizar a multiplicação e simplificação:** \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Portanto, a composição das funções é: \[ f \circ g(x) = 6x - 5 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Para encontrar \( f \circ g(x) \), precisamos substituir \( g(x) \) na função \( f(x) \). Primeiro, calculamos \( g(x) \): \[ g(x) = 2x - 3 \] Agora, usamos isso como entrada para a função \( f(x) \): \[ f(g(x)) = f(2x - 3) \] Agora, substituímos \( 2x - 3 \) na expressão de \( f(x) \): \[ f(2x - 3) = 3(2x - 3) + 4 \] \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Portanto, \( f \circ g(x) = 6x - 5 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy